2011
DOI: 10.1007/s00198-011-1691-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustained efficacy and safety of bazedoxifene in preventing fractures in postmenopausal women with osteoporosis: results of a 5-year, randomized, placebo-controlled study

Abstract: The findings support a sustained anti-fracture effect of bazedoxifene on new vertebral fractures in postmenopausal osteoporotic women and on non-vertebral fractures in the higher-risk subgroup of women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 35 publications
9
63
0
7
Order By: Relevance
“…It appears that this SERM does not stimulate but rather antagonizes endometrial growth in postmenopausal women (Ronkin et al, 2005). Other clinical trials revealed that bazedoxifene treatment prevents bone loss and reduces bone turnover with similar efficacy to raloxifene in postmenopausal women who have normal-to-low BMD without increasing mammographic breast density, the incidence of hot flashes Silverman et al, 2008Silverman et al, , 2012Archer et al, 2009;Harvey et al, 2009;Kanis et al, 2009;Pinkerton et al, 2009a;Christiansen et al, 2010;Bachmann et al, 2011;de Villiers et al, 2011;Xu et al, 2011). Bazedoxifene also displays efficacy for treating vasomotor symptoms and preventing endometrial hyperplasia in postmenopausal women Pinkerton et al, 2009b).…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…It appears that this SERM does not stimulate but rather antagonizes endometrial growth in postmenopausal women (Ronkin et al, 2005). Other clinical trials revealed that bazedoxifene treatment prevents bone loss and reduces bone turnover with similar efficacy to raloxifene in postmenopausal women who have normal-to-low BMD without increasing mammographic breast density, the incidence of hot flashes Silverman et al, 2008Silverman et al, , 2012Archer et al, 2009;Harvey et al, 2009;Kanis et al, 2009;Pinkerton et al, 2009a;Christiansen et al, 2010;Bachmann et al, 2011;de Villiers et al, 2011;Xu et al, 2011). Bazedoxifene also displays efficacy for treating vasomotor symptoms and preventing endometrial hyperplasia in postmenopausal women Pinkerton et al, 2009b).…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…2 Bazedoxifene is not approved as a single agent ingredient; however, there are studies supporting its potential use as monotherapy in the prevention and treatment of osteoporosis in postmenopausal women. [3][4][5][6][7][8][9][10][11][12][13][14][15] Raloxifene, another SERM, is approved 1 Clinical effects observed in animal models include prevention of ovariectomy-associated body weight increases, 17 protection against ovariectomyassociated bone loss, [18][19][20] increased bone mineral density, 21,22 and increased bone compressive strength.…”
Section: Indicationsmentioning
confidence: 99%
“…The incidence of pulmonary or retinal vein thrombosis was similar among groups. None of these studies 48,51 showed a higher incidence of adverse effects on the cardiovascular system with bazedoxifene, including myocardial infarction and stroke. Also there seems to be a favorable effect (or at least without adverse significant effect) on the lipid profile.…”
Section: -50mentioning
confidence: 99%